(untitled) (Journal of Universal Excellence, 2026)
Research question (RQ): The area of a human, organizations and Organizations is complex and with new aspects of 4.0 organization even more complex. We did an autopoietic outline with horizontal and vertical view of a researcher who sticks to humanity of an individual and organizations. The research question stems from the central study: Which are building blocks of autopoises in a modern and which in 4.0 organization? Purpose: To detect, recognize, research principles of autopoiesis and setting building blocks of autopoiesis in organizations. We are interested in a human in organization, in interpersonal co-dependance on micro and macro level. Inside this more and more virtual organization we are studying a human, humanity and human potential as a creative potential of humane organization. Method: Action research with mixed methods for comprehensive study of autopoietic principle and methodology of setting the autopoietic building blocks. We used Atlas.ti software and methodological informational software »Informational graph of Autopoiesis - IGA«. Validation was carried out with double triangulaton (static and dynamic view). Results: We formed and validated four directional building blocks and 36 process building blocks, which are shown in a human as: emotions, thinking, directing and activity. Significant difference in two process building blocks of autopoiesis in modern and 4.0 organization confirms the set thesis statement that the building blocks of modern and 4.0 organization are different. We detected that in 4.0 organization the process building blocks of self-/co-feeling and self-/co-referencing aregetting weaker. With results we claim that 4.0 organization is oriented mostly towards action and is getting stronger in improved communication. However, it decreases in emotions and thinking of a human in an organization. Organization: Results can serve as a guideline and challenge to humane organizations. We present the challenge how – by knowing horizontal and vertical laws of a human – we can »control« 4.0 organization. The research contributes to awareness of a human and to transformation of allopoietic to more and more autopoietic organizations, which repesents a move from mechanistic to humane paradigm. Society: Accepting autopoiesis on all levels of society and consequently emerging organizations, as well as society as a whole. The final result is to influence by autopoiesis the cultural development of society in the sense of connecting science, art, high technologies and spirituality. Originality: Interlacement of horizontal and vertical areas of theory, multilayer view of research of organization with »IGA« and validation with double triangulation. Limitations/Future resesarch: Relatively modest range of references on the subject of Industry 4.0. Research of directional and process building blocks in »IGA«. Founding an institute for studying autopoiesis on all levels of society.